2020
DOI: 10.1371/journal.pntd.0008240
|View full text |Cite
|
Sign up to set email alerts
|

Mycetoma in Uganda: A neglected tropical disease

Abstract: Mycetoma is considered a neglected tropical disease globally. However, data on its burden and the associated complications in Uganda are limited. Hence we aimed to estimate its burden in Uganda. Firstly, a systematic PubMed search for all studies of any design on mycetoma in Uganda without restriction to the year of publication was conducted. A retrospective review of all the biopsy reports at the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 14 publications
3
29
0
Order By: Relevance
“…Another recent paper by Kwizera and colleagues on mycetoma in Uganda [43] emphasizes the propensity of this NTD to be misdiagnosed. In our original literature review, only 30 cases were identified for Uganda, from only two case series published in 1958 [44] and 1965 [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another recent paper by Kwizera and colleagues on mycetoma in Uganda [43] emphasizes the propensity of this NTD to be misdiagnosed. In our original literature review, only 30 cases were identified for Uganda, from only two case series published in 1958 [44] and 1965 [45].…”
Section: Discussionmentioning
confidence: 99%
“…In our original literature review, only 30 cases were identified for Uganda, from only two case series published in 1958 [ 44 ] and 1965 [ 45 ]. However, when Kwizera and colleagues reviewed the biopsy reports of the Pathology Department at Makerere University from 1950 to 2019, they found an additional 249 cases; the authors cite a low index of suspicion for mycetoma amongst clinicians as a reason for this [ 43 ]. The perceived rarity of mycetoma compounded underdiagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that almost 35% of subjects with CPA might be wrongly treated with anti-TB medication despite the lack of microbiological evidence [ 22 ]. This is also very common in resource-limited settings where the index of clinical suspicion for fungal infections is very low [ 13 , 23 ] and the diagnostic capacity for mycoses is lacking. A recent paper from our setting showed that “using freely available online materials on medical mycology can enhance teaching and learning of medical mycology" [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neglected tropical diseases (NTD’s) such as lymphatic filariasis, leprosy, schistosomiasis, soil-transmitted helminths and sleeping sickness remain a big problem in the country affecting mainly rural poor communities [ 16 ]. The burden of fungal infections is also high with an estimated 2.5 million fungal infections per year in Uganda [ 17 ], yet the index of clinical suspicion remains low [ 18 , 19 ]. The growing burden of NCDs could be attributed to change in life style and the environment that necessitates research investigations tailored to the local burden.…”
Section: Main Textmentioning
confidence: 99%